Butyrate Inhibits Indices of Colorectal Carcinogenesis via Enhancing α‐Ketoglutarate‐Dependent DNA Demethylation of Mismatch Repair Genes. Issue 10 (26th April 2018) - Sun, Xiaofei; Zhu, Mei‐Jun
Abstract : Scope: Butyrate, the fermentation end product of gut microbiota in the colon, is known for its antitumor effects, but the mechanisms remained to be defined. α‐ketoglutarate (α‐KG) mediates DNA demethylation and aberrant epigenetic modifications are associated with carcinogenesis. The objectives of this study are to evaluate the effects of butyrate on α‐KG mediated epigenetic modification in colorectal adenocarcinoma HT‐29 and Caco‐2 cells. Methods and results: Butyrate suppressed proliferation, potentiated differentiation, and induced apoptosis in both HT‐29 and Caco‐2 cells, associated with enhanced expression of isocitrate dehydrogenase 1 (IDH1) and pyruvate dehydrogenase. Furthermore, butyrate upregulated acetyl‐CoA and α‐KG, concomitant with enhanced histone acetylation and DNA demethylation in the promoter of DNA mismatch repair (MMR) gene. Knocking down IDH1 abolished the positive effects of butyrate on CRC apoptosis and MMR protein expression, in conjunction with reduced α‐KG content. Importantly, α‐KG supplementation recovered the beneficial effects of butyrate in IDH1‐deficient cells. Conclusion: In summary, butyrate inhibits indices of colorectal carcinogenesis in an α‐KG‐dependent manner. Abstract : Butyrate upregulates pyruvate dehydrogenase (PDH) and isocitrate dehydrogenase 1 (IDH1), which then increases the contents of their metabolites, acetyl‐CoA and α‐ketoglutarate (α‐KG), respectively. α‐KG promotes DNA demethylation in the promoter of DNA mismatch repair (MMR) genes. Acetyl‐CoA enhances the histone acetylation in colorectal cancer cells. Histone acetylation and DNA demethylation jointly promote MMR protein expression, which suppress colorectal carcinogenesis.